Diabetes immunity-modulated multifunctional hydrogel with cascade enzyme catalytic activity for bacterial wound treatment. (October 2022) - Deng, Mengyuan; Zhang, Meng; Huang, Rong; Li, Hongyuan; Lv, Wenxin; Lin, Xiaojun; Huang, Rongqin; Wang, Yi
Abstract: Diabetes immunity-modulated wound treatment in response to the varied microenvironments at different stages remains an urgent challenge. Herein, glucose oxidase (GOx) and quasi-amorphous Fe2 O3 are co-incorporated into Zn-MOF nanoparticle (F-GZ) for cascade enzyme catalytic activities, where not only the high blood glucose in the wound is consumed via the GOx catalysis, but also the effective anti-bacteria is achieved via the degradedly released Zn 2+ synergistically with the catalytically produced ·OH during the bacterial infection period with the low pH microenvironment. Simultaneously, the reactive oxygen species scavenging and hypoxia relief is realized via catalyzing H2 O2 to produce O2 at the relatively elevated pH environment during the wound recovery period. Subsequently, a multifunctional hydrogel with injectable, self-healing and hemostasis abilities, as well as uniformed F-GZ loading is prepared via the copolymerization reaction. This hydrogel behaves as F-GZ but reduces the toxic effects, which thus accelerates the diabetic wound healing. More importantly, this hydrogel is found to modulate the diabetes immunity possibly mediated via the released Zn 2+, which thus contributes to the recovered pancreatic islet functions with improved glucose tolerance and increased insulin secretion for enhanced diabetic wound treatments. This work initiates a new strategy for simultaneous diabetic wound management and also suggests a potential way for diabetic immunity modulation.